Self‐medication of anaphylactic reactions due to Hymenoptera stings—an EAACI Task Force Consensus Statement. Issue 7 (29th April 2016) - Bilò, M. B.; Cichocka‐Jarosz, E.; Pumphrey, R.; Oude‐Elberink, J. N.; Lange, J.; Jakob, T.; Bonadonna, P.; Fernandez, J.; Kosnik, M.; Helbling, A.; Mosbech, H.; Gawlik, R.; et al.
Abstract: An anaphylactic reaction due to a Hymenoptera sting is a clinical emergency, and patients, their caregivers as well as all healthcare professionals should be familiar with its recognition and acute management. This consensus report has been prepared by a European expert panel of the EAACI Interest Group of Insect Venom Hypersensitivity. It is targeted at allergists, clinical immunologists, internal medicine specialists, pediatricians, general practitioners, emergency department doctors, and any other healthcare professional involved. The aim was to report the scientific evidence on self‐medication of anaphylactic reactions due to Hymenoptera stings, to inform healthcare staff about appropriate patient self‐management of sting reactions, to propose indications for the prescription of an adrenaline auto‐injector (AAI), and to discuss other forms of medication. First‐line treatment for Hymenoptera sting anaphylaxis is intramuscular adrenaline. Prescription of AAIs is mandatory in the case of venom‐allergic patients who suffer from mast cell diseases or with an elevated baseline serum tryptase level and in untreated patients with a history of a systemic reaction involving at least two different organ systems. AAI prescription should also be considered in other specific situations before, during, and after stopping venom immunotherapy.